Peptidylarginine Deiminase 2 in Host Immunity: Current Insights and Perspectives - Wu, Zhenyu; Li, Patrick; Tian, Yuzi; Ouyang, Wenlu; Ho, Jessie Wai-Yan; Alam, Hasan B.; Li, Yongqing (Frontiers in Immunology, 2021)
Peptidylarginine deiminases (PAD) are a group of enzymes that catalyze the post-translation modifications of proteins by converting arginine residues into citrullines. Among the five members of PAD family, PAD2 and PAD4 are the most frequently studied because of their abundant expression in immune cells. An increasing number of studies have identified PAD2 as an essential factor in the pathogenesis of many diseases. The success of preclinical research targeting PAD2 highlighted the therapeutic potential of PAD2 inhibition, particularly in sepsis and autoimmune diseases. However, the underlying mechanisms via which PAD2 mediates host immunity remain largely unknown. In this review, we will discuss the role of PAD2 in different types of cell death signaling pathways and the related immune disorders compared with function of PAD4, providing novel therapeutic strategies for PAD2-associated illnesses.